Perencanaan Lanskap untuk Pengembangan Wisata di Gunung Padang, Kota Padang, Sumatera Barat - Khairani, Ulfa; Yusiana, Lury Sevita; Mayadewi, Ni Nyoman Ari (Jurnal Arsitektur Lansekap; Vol.7, No.2, Oktober 2021DO - 10.24843/JAL.2021.v07.i02.p03, 2021)
Landscape Planning for Tourism Development in Gunung Padang, Padang City, West Sumatra. Gunung Padang is one of the tourist attractions located in the city of Padang, this area is surrounded by vegetation and animals that live well, so this tourist attraction is included in the protected and preserved tourist areas. It has tourism potential such as tourist attractions, tourist activities, and tourism supporting facilities. Various tourism potentials have not been developed as a whole by the management. Based on this, it is necessary to optimize and provide recommendations in order to be developed. The purpose of this research is to develop landscape planning to support tourism development in Gunung Padang, Padang City, through the stages of preparation, inventory, analysis, synthesis, and planning aimed at sustainable tourism development. Analysis and synthesis are carried out to produce basic concepts and concepts of tourism development. The final product of this research is the planned tourism development site in Gunung Padang. The division of space is based on the needs and according to the conditions owned by the tourist area in order to support security and comfort in travel activities. The final result of this research is a map of the plan of attractions and tourist activities, as well as a map of the layout plan of tourist facilities in Gunung Padang.